Critical parameter calculation of a binary melt crystallization in stationary regime - Kanishchev, V.N.; Barannik, S.V. (Functional Materials, 2004)
Taking into account the latent melting heat and the heat conductivity differences between the solid and liquid phases, the stationary heat and mass transfer problem in a bounded domain region of a crystal/melt system has been solved under linear approximation with respect to the crystallization front non-flatness. The region of the problem input parameters has been shown to be subdivided into two sub-regions, a subcritical (where the solution can be a flat one only) and a supercritical one (where the crystallization front can take a cellular structure). The derived condition of the transition to the supercritical crystallization regime corresponds exactly to the modified criterion of concentration overcooling that is known in the cellular crystal growth theory.